Analisis Faktor Penyebab Terjadinya Missfile Berkas Rekam Medis Rawat Inap di Rumah Sakit PHC Surabaya Tahun 2020 - Muzaffatul Hasan; Efri Tri Ardianto; Dony Setiawan Hendyca Putra (Politeknik Negeri Jember, 2020)
Based on the results of a preliminary study conducted at the Surabaya PHC Hospital in 2020 in the filing section of the Surabaya PHC Hospital there was still a missfile incident in the inpatient medical record file. Missfile is an incident where the medical record file is not found because of an error in placing the medical record file on the filing rack, this can cause a decrease in the quality of services provided. The importance of the role of medical record documents in creating information that is sustainable, researchers interested in examining the problem of the occurrence of errors (missfile). This study aims to analyze the analysis of the factors that cause the medical file file missfile in Surabaya PHC Hospital using the PTA (Problem Tree Analysis) method. This type of research is qualitative with observation and interview data collection techniques. The results of this study are the main factors causing missfile is the behavior of officers, level 1 contributing factors are There is no responsible person in the inpatient medical record file storage, less maximum use of facilities and infrastructure and SOP (Standard Operating Procedure) storage of inpatient medical record files never been socialized. Factors causing level 2 are the need for officers to be responsible for storing inpatient medical record files, lack of knowledge about tracers and the existence of maps in inpatient medical record files, lack of application of SOP (Standard Operating Procedure) does not match the reality because it is only limited accreditation fulfillment requirements. So the implementation of inpatient medical record file storage in Surabaya PHC Hospital is still not good, so that there is still a missfile. The hospital should increase the number of workers in the medical records unit in the filing section, conduct socialization on the importance of using tracers, accelerate the procurement of inpatient medical record file folders and apply SOPs as guidelines for officers in carrying out work. So that the implementation of inpatient medical record file storage for the better.